Platelet Distribution in Rabbits Following lnfusion of Liposomes - Doerschuk, Claire M; Gie, Robert P; Bally, Marcel B; Cullis, Pieter R; Reinish, Lawrence W (Thrombosis and Haemostasis, 1989)
This investigation determined the organ distribution of liposomes containing egg phosphatidylcholine and cholesterol with egg phosphatidylglycerol (PG liposomes) or without (PC liposomes) and the effect of each liposome on platelet distribution in rabbits. Eight minutes after51 chromium-labelled platelets were given intravenously, either saline (n = 7), iodinated PG liposomes (n = 5) or iodinated PC liposomes (n = 5) were infused. T\ro minutes later the organ distribution of 51Cr-platelets and 125I-liposomes were compared. The PG liposomes produced a 41λ5% reduction in circulating platelet counts while PC liposomes did not. The PG liposomes decreased circulating 51Cr-platelets by a factor of 2 and increased platelet recoveries in the liver and lungs. The increased platelet recovery in the liver was associated with a greater PG liposome recovery. When animals receiving PG liposomes were studied over 60 minutes, both the labelled and unlabelled platelet counts returned to control values by 30 minutes and the 51Cr-platelet distribution between organs was similar to control values. These data indicate that platelets and PG liposomes initially sequester together and that this plateletliposome interaction is specific for PG liposomes. However, the platelet sequestration is transient and by 60 minutes the platelets were released and circulating.
Keywords: Platelets; Liposomes; Platelet-endothelial interactions; Liposome biodistribution; Radiolabelled platelet kinetics; Platelet-liposome interactions